Multi-scale simulation of the experimental response of ion-irradiated zirconium carbide: Role of interstitial clustering. (1st January 2016) - Pellegrino, Stéphanie; Crocombette, Jean-Paul; Debelle, Aurélien; Jourdan, Thomas; Trocellier, Patrick; Thomé, Lionel
Abstract: The response of zirconium carbide to heavy-ion irradiation at room temperature has been studied by X-ray diffraction, ion channeling and transmission electron microscopy. Below 5 × 10 14  cm −2, we observe a build-up of elastic strain with increasing fluences. At this threshold fluence the strain is released and important dechanneling appears as well as visible TEM damage. With increasing fluence, this damage is found to spread in the material deeper than the depth of direct damaging by the ion beam. These experimental observations are reproduced and explained by Density Functional Theory informed Rate Equation Cluster Dynamics simulations. Simulations show that the response of ZrC upon ion-irradiation is driven by the diffusion and clustering of interstitials. The two-step evolution seen in experiments stems from the growth of interstitial clusters with a concomitant starvation of the smallest clusters induced by the continuous accumulation of vacancies. The damaging of the material beyond the range of primary damage is driven by diffusion of interstitials. Graphical abstract: